Analysis of Mangrove Forest Community Structure in Coastal Area of Kerang Beach, Banten Province, Indonesia - Rega Permana; Aulia Andhikawati (Jurnal Perikanan dan Kelautan, 2026)
Mangrove community is part of an important tropical ecosystem in coastal areas which own multiple biological and ecological function thus reinforced coastal resiliency both socially and economically.  Banten Province, the most western part of the Java Islands possesses a high risk of natural disaster due to its location which right next to the sunda strait where the Krakatau Volcanic Mountains belongs, thus need a strong and healthy mangrove community as a natural barrier to high wave. This research aimed to analyse the condition of mangrove vegetation of Kerang Beach which located in the coastal of Banten Province. The research used line transect method and observed all the vegetation growth stage including tree, stake and seed. The results showed that Avicennia marina is the most frequent and densest species in the location with value of Relative Frequency 35-54% and Relative Density 44-84% both for tree, stake and seed. The research showed that overall, the mangrove community in the sampling location still in a stable category with Diversity index 1.135, Evenness index 0.633 and Dominance Index 0.408, which indicated that the condition is moderately stable